Analisis Faktor-Faktor Yang Menentukan Mitra Binaan SMES Bergabung dalam Program Bantuan Teknis Bank Indonesia - Pangau, Noula trine (Universitas Sam Ratulangi, 2017)
The objective of this study is to determine the factors which could determine the partners UMKM join in a program of technical assistance to Bank Indonesia. The object of this Study is that this Study takes the object of the UMKM in the whole city and regency in the Province of North Sulawesi recorded in the Representative Office of Bank Indonesia North Sulawesi Province. The population in this study is 50 (fifty) SMES assisted Bank Indonesia. As for the sampling method in this research used population studies or the census study where all members of the population sampled. Thus the sample in this study is 32 (thirty two) SMES assisted Bank Indonesia. Based on the results of the analysis of test factors, it was found that there are three factors that be a factor that encourages SMES to join the program of Bank IndonesiaKeywords: Factor Analysis, SMEs.